2007
DOI: 10.1007/s11431-007-2018-5
|View full text |Cite
|
Sign up to set email alerts
|

Ocean waves propagating over a porous seabed: Residual and oscillatory mechanisms

Abstract: Two mechanisms for the wave-induced pore pressures in a porous seabed, i.e. oscillatory and residual excess pore pressures, have been observed in laboratory experiments and field measurements. Most previous investigations have focused on one of the mechanisms individually. In this paper, an analytical solution for the wave-induced residual pore pressure, which is not available yet, is derived, and compared with the existing experimental data. With the new solution, a parametric analysis is performed to clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…As such, soil scour (general and local scour) should be taken into account when evaluating the foundation instability [31]. In the shallow waters, the waves and currents are always coexisting; the wave-induced soil liquefaction [115] would be coupled with the local scouring process, which further complicates the failure mechanism of foundations.…”
Section: Discussionmentioning
confidence: 99%
“…As such, soil scour (general and local scour) should be taken into account when evaluating the foundation instability [31]. In the shallow waters, the waves and currents are always coexisting; the wave-induced soil liquefaction [115] would be coupled with the local scouring process, which further complicates the failure mechanism of foundations.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the accumulated pore pressure and liquefaction were important for large waves and became apparent with increases in the relative water depth (d/L) and wave steepness (H/L). In this article, the soil in the seabed was sand, and the permeability was much larger than it was in the Jeng et al (2007) study. Also, the water depth was not greater than 20 m in liquefied cases, and the steepness of most waves (H/L) was small.…”
Section: Introductionmentioning
confidence: 73%
“…It generally increases at the initial period of wave loading until accumulating to a certain value at which it primarily remains. Jeng et al (2007) analyzed the effects of residual mechanism on pore pressure and liquefaction in the seabed by analytical methods. They found that the accumulated pore pressure and liquefaction were important for large waves and became apparent with increases in the relative water depth (d/L) and wave steepness (H/L).…”
Section: Introductionmentioning
confidence: 99%
“…Jeng et al [8] discussed two mechanisms for wave-induced pore pressures in a porous seabed, i.e., oscillatory, residual excess pore pressures, and an analytical solution for the waveinduced residual pore pressure was derived. Using the residual pore-pressure analytical solution [8], the process of wave-induced soil erosion was investigated. Then, the parametric studies were In this paper, a three-phase soil model (soil skeleton, pore fluid, and fluidized soil particles) was established to study the soil erosion process induced by waves in the silty sand seabed.…”
Section: Introductionmentioning
confidence: 99%
“…COMSOL Multiphysics is a kind of finite element method (FEM) software which is developed by COMSOL INC found in Stockholm, Sweden. Jeng et al [8] discussed two mechanisms for wave-induced pore pressures in a porous seabed, i.e., oscillatory, residual excess pore pressures, and an analytical solution for the wave-induced residual pore pressure was derived. Using the residual pore-pressure analytical solution [8], the process of wave-induced soil erosion was investigated.…”
Section: Introductionmentioning
confidence: 99%